Quercetin Declines Apoptosis, Ameliorates Mitochondrial Function and Improves Retinal Ganglion Cell Survival and Function in In Vivo Model of Glaucoma in Rat and Retinal Ganglion Cell Culture In Vitro - Gao, Feng-Juan; Zhang, Sheng-Hai; Xu, Ping; Yang, Bo-Qi; Zhang, Rong; Cheng, Yun; Zhou, Xu-Jiao; Huang, Wan-Jing; Wang, Min; Chen, Jun-Yi; Sun, Xing-Huai; Wu, Ji-Hong (Frontiers in Molecular Neuroscience, 2017)
Glaucoma is a progressive neuropathy characterized by the loss of retinal ganglion cells (RGCs). Strategies that delay or halt RGC loss have been recognized as potentially beneficial for rescuing vision in glaucoma patients. Quercetin is a natural and important dietary flavonoid compound, widely distributed in fruits and vegetables. Mounting evidence suggests that quercetin (Qcn) has numerous neuroprotective effects. However, whether Qcn exerts neuroprotective effects on RGC in glaucoma is poorly understood. In this study, we investigated the protective effect of Qcn against RGC damage in a rat chronic ocular hypertension (COHT) model in vivo and hypoxia-induced primary cultured RGC damage in vitro, and we further explored the underlying neuroprotective mechanisms. We found that Qcn not only improved RGC survival and function from a very early stage of COHT in vivo, it promoted the survival of hypoxia-treated primary cultured RGCs in vitro via ameliorating mitochondrial function and preventing mitochondria-mediated apoptosis. Our findings suggest that Qcn has direct protective effects on RGCs that are independent of lowering the intraocular pressure. Qcn may be a promising therapeutic agent for improving RGC survival and function in glaucomatous neurodegeneration.